Exploiting Pre-Existing Beliefs - Ahmed E. Taha (Washington University Law Review, 2019)
Advertisements and product labels for a wide range of consumer and investment products have highlighted product characteristics that some people erroneously believe make them superior to competitor goods and services. This article argues that these advertisements and labels are deceptive because they imply that those erroneous beliefs are accurate even if they don’t mention the erroneous beliefs. Moreover, these advertisements and labels can deceive even those individuals who have no pre-existing beliefs regarding the highlighted characteristics. This deception distorts purchasing and investing decisions, causing consumers and investors financial loss, reduced satisfaction, and sometimes even physical harm. Because these advertisements and labels are used for many different products, they are regulated by a number of federal agencies, whose regulatory approach often requires the advertisement or label to include a disclaimer of the erroneous belief. This article examines the effectiveness of such disclaimers and other possible regulatory approaches. It argues that often a stronger approach is justified: a prohibition against highlighting a product characteristic about which consumers or investors have an erroneous belief.
Keywords: Advertising law; Marketing law; Misleading ads; Erroneous beliefs; Exploiting pre-existing beliefs; Deceptive ads